(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Despite the constantly increasing spending on digital advertising, the efficiency of the ecosystem’s operating is becoming more apparent. This is because just a tiny portion of the money spent by businesses on different kinds of digital advertising yields the desired outcomes. In today’s corporate world, the term "digital marketing" is a buzzword. Because of its cost efficiency, digital advertising, which is a small portion of it, has become the most frequently discussed and worked on. Communication between the customer and the seller has taken on a completely new meaning in the internet era. As more individuals become computer aware, the internet is developing as a powerful advertising medium. The purpose of this article is to explain the efficacy of digital advertising in terms of generating awareness, interest, and preference, as well as giving product information and encouraging purchase. The most popular ad formats is also explained. Consumers consider digital advertising to be helpful and interesting, according to the research.